2021
DOI: 10.3390/molecules26040882
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and Functional Analyses Implicate Potential Roles for EOGT and L-fringe in Pancreatic Cancers

Abstract: Notch signaling receptors, ligands, and their downstream target genes are dysregulated in pancreatic ductal adenocarcinoma (PDAC), suggesting a role of Notch signaling in pancreatic tumor development and progression. However, dysregulation of Notch signaling by post-translational modification of Notch receptors remains poorly understood. Here, we analyzed the Notch-modifying glycosyltransferase involved in the regulation of the ligand-dependent Notch signaling pathway. Bioinformatic analysis revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…First of all, our pan-cancer analysis showed that EOGT was highly expressed in five types of cancer, namely, CHOL, HNSC, KIRC, HCC, and THCA. However, there were studies that showed that EOGT expression was increased in PAAD ( 9 , 10 ), which contradicted with our results, because they did not consider the classical subtype of PAAD. Results from GEO and Oncomine consistently demonstrated that EOGT expression was obviously elevated in HCC samples.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…First of all, our pan-cancer analysis showed that EOGT was highly expressed in five types of cancer, namely, CHOL, HNSC, KIRC, HCC, and THCA. However, there were studies that showed that EOGT expression was increased in PAAD ( 9 , 10 ), which contradicted with our results, because they did not consider the classical subtype of PAAD. Results from GEO and Oncomine consistently demonstrated that EOGT expression was obviously elevated in HCC samples.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, KM survival analysis using the KM plotter and CPTAC further proved that elevated EOGT expression was closely linked to poor OS and RFS in HCC samples. Moreover, it was reported that low expression of both EOGT and LFNG was associated with favorable OS in pancreatic ductal adenocarcinoma patients ( 9 ). In a recent study, IHC staining in sequencing samples confirmed that EOGT was linked to poor OS in pancreatic cancer ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal expression of Notch receptors, ligands, and their downstream target genes in pancreatic ductal adenocarcinoma (PDAC) suggests that Notch signaling plays a role in the development and progression of pancreatic tumors [ 149 , 150 , 151 ]. O -GlcNAcylation also plays an important role in PDAC development [ 152 ]. The expression levels of EOGT and Shc SH2-binding protein 1 (SHCBP1) were significantly increased in patients with PDAC, which was associated with a worse prognosis.…”
Section: Significance Of Notch O -Glycosylation In...mentioning
confidence: 99%
“…Barua et al reported that the O-GlcNAcylation of Notch receptor participated in the regulation of proliferation and migration of Panc-1 pancreatic cancer cells. 35 Stateva and Villalobo reported the presence of O-GlcNAcylated EGFR in the A431 skin squamous and the A549 lung cancer cell lines. 5 Moreover, Wang et al observed that knockdown of OGT in the 786-O kidney cancer cell line led to a downregulation of EGFR O-GlcNAcylation.…”
Section: Potential Applications Of the Nanotechnique For Targeting O-...mentioning
confidence: 99%